2021
DOI: 10.1111/jocn.15745
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intersectionality on nursing leadership, empowerment and culture: A case study exploring nurses and managers’ perceptions in an acute care hospital in Aotearoa, New Zealand

Abstract: Aim: This study determines whether the culture within an acute care hospital empowers 'all' nurses to be leaders by exploring intersectionality and nursing leadership in the context of the social environment.Background: Nurses practice leadership in their day-to-day activities as clinical leaders alongside traditional roles of management and leadership. However, some nurses do not acknowledge nursing work as leadership activity, nor is it seen so by others where hierarchical leadership approaches remain preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(69 citation statements)
references
References 49 publications
1
61
0
Order By: Relevance
“…Barriers on the level of the care organisation and its management point out that there is a lack of leadership and guidance towards culturally sensitive care and a lack of organisational policy towards culturally sensitive care when patient and healthcare professionalfrom different ethnic-cultural backgrounds-interact with each other. Although research has proven that the role of the care organisation and the management is very important to support the healthcare professionals in daily care practice and to strengthen structural changes (Aspinall et al, 2021;McClimens et al, 2014), our study shows that there is little support from the employer or the manager, and the responsibility to find flexible solutions or to think out of the box lies with the individual healthcare provider. Markey et al (2012) claims the whiteness of the care institutions goes unnoticed as the prevailing framework, which plays an important role in the deceleration of structural changes.…”
Section: Discussionmentioning
confidence: 64%
“…Barriers on the level of the care organisation and its management point out that there is a lack of leadership and guidance towards culturally sensitive care and a lack of organisational policy towards culturally sensitive care when patient and healthcare professionalfrom different ethnic-cultural backgrounds-interact with each other. Although research has proven that the role of the care organisation and the management is very important to support the healthcare professionals in daily care practice and to strengthen structural changes (Aspinall et al, 2021;McClimens et al, 2014), our study shows that there is little support from the employer or the manager, and the responsibility to find flexible solutions or to think out of the box lies with the individual healthcare provider. Markey et al (2012) claims the whiteness of the care institutions goes unnoticed as the prevailing framework, which plays an important role in the deceleration of structural changes.…”
Section: Discussionmentioning
confidence: 64%
“…Aspinall et al (2021) investigating intersectionality and nursing leadership describes how nurses did not acknowledge themselves as clinical leaders neither as a professional cadre were they recognised as so by other health professionals who ignored them in multidisciplinary meetings and during ward rounds unless they held a manager's title. English fluency was associated with perceptions of levels of competence and impeded career progression in several studies (Aspinall et al, 2021; Isaac, 2020; Semu, 2020). Experiences unearthed in Semu's study P.8 led them to a disconcerting description of nursing, stating, ‘The nursing profession has become the new ghetto for immigrant women of colour’.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the reflections above, the results of the literature review show that there is a need for researchers to engage themselves with theoretical frameworks to address the issue of nurses' agency. The theoretical lenses of critical realism as used by Goodman ( 2017 ) and Williams et al ( 2016 ) have shown their value in highlighting the multiple ways in which agency is harnessed by nurses to confront forms of domination (Aspinall et al, 2019 , 2021 ; Schiller, 2016 ). However, critical theory lenses have been the ones that have made the most forceful contributions toward nurses' emancipation (Chulach & Gagnon, 2016 ; McMillan & Perron, 2020 , 2021 ; Paloniemi & Collin, 2012 ; Perron, 2013 ).…”
Section: Discussionmentioning
confidence: 99%